2016
DOI: 10.2147/jmdh.s105000
|View full text |Cite
|
Sign up to set email alerts
|

A simple dietary assessment tool to monitor food intake of hospitalized adult patients

Abstract: Background/objectivesMonitoring food intake of patients during hospitalization using simple methods and minimal training is an ongoing problem in hospitals. Therefore, there is a need to develop and validate a simple, easy to use, and quick tool that enables staff to estimate dietary intake. Thus, this study aimed to develop and validate the Pictorial Dietary Assessment Tool (PDAT).Subjects and methodsA total of 37 health care staff members consisting of dietitians, nurses, and serving assistants estimated 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
(39 reference statements)
0
23
0
2
Order By: Relevance
“…26 This scale has been adapted and modified into studies in the United States, Canada, Indonesia, and Israel. [27][28][29][30] The researcher observed the leftovers before recording the data into the scale. The scale comprises levels of all not eaten = 100%, one bite eaten = 80%, 3/4 left = 60%, 1/2 left = 40%, 1/4 left = 20%, and none left = 0%.…”
Section: Part C: Comstock 6-point Scalementioning
confidence: 99%
See 1 more Smart Citation
“…26 This scale has been adapted and modified into studies in the United States, Canada, Indonesia, and Israel. [27][28][29][30] The researcher observed the leftovers before recording the data into the scale. The scale comprises levels of all not eaten = 100%, one bite eaten = 80%, 3/4 left = 60%, 1/2 left = 40%, 1/4 left = 20%, and none left = 0%.…”
Section: Part C: Comstock 6-point Scalementioning
confidence: 99%
“…The results identified a weak negative correlation between the 2 variables (r = -0.16, n = 189, P = 0.03), with higher age being associated with lower satisfaction with the hospital foodservice. Subjects were divided into 3 age groups (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), and 56-65 years). The independent sample t test results indicated no significant difference in scores for males (M = 2.62, SD = 0.74) and females (M = 2.65, SD = 0.77); t (187) = 0-.27, P = 0.79 (two-tailed).…”
Section: Patient Satisfaction According To Various Factorsmentioning
confidence: 99%
“…In the second period, the first group used PDAT and the second group used modified Comstock for two weeks. The sample size calculation for comparing means of two groups indicated that a minimum sample size of 10 assessors was required to detect a mean difference in accuracy between the test method and reference method of 13 kcal (given a standard deviation (SD) of the difference between the two value of 10 kcal) [ 18 ] with 90% power and a type I error probability of ≤0.05. Each staff member measured three patients for two periods, so that a total of 132 patients were included.…”
Section: Methodsmentioning
confidence: 99%
“…Such overestimation can allow problems to go unrecognized by nursing staff, thus preventing follow-ups with further nutritional assessment [ 9 , 17 ]. We have successfully developed and validated a dietary assessment tool for use in a clinical setting, the Pictorial Dietary Assessment Tool (PDAT) [ 18 ]. This method is a simple, easy-to-use, quick tool that enables staff to estimate dietary intake and can easily be integrated into dietitians’ evaluations of patients during their stay in the hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation